From hoping to help: Identifying and responding to suicidality amongst victims of domestic abuse - Munro, Vanessa E. (International review of victimology, 2020)
This article analyses findings from a large-scale study conducted in England and Wales into the prevalence of, and mediators and moderators of risk in relation to, suicidality amongst victims of domestic abuse. The authors tracked (disclosed) experiences of suicidal ideation or suicide within a sample of more than 3,500 domestically abused adults and explored factors that appeared to be correlated with a presence of suicidality amongst this constituency. This analysis was triangulated with a series of 20 semi-structured interviews which explored on-the-ground challenges in relation to the identification of, and support provision for, this vulnerable group, and which also included reflection on the difficulties experienced by staff as a consequence of the emotionally demanding nature of their interactions with such clients. Based on their findings, in this article, the authors underscore the need for more effective multi-agency cooperation, for greater priority to be given to self-harm and suicidality in risk-assessment processes, and for sustainable resourcing of domestic abuse service providers. In a context in which suicidality was correlated with experiences of isolation and hopelessness, they also emphasise the importance of appropriate and effective engagement by state agencies and those professionals tasked with intervening to help victims of domestic abuse.